Kekuatan Pembuktian Alat Bukti Elektronik Dalam Hukum Acara Perdata - Soroinda, Disriani Latifah; Nasution, Anandri Annisa Rininta Soroinda (Jurnal Hukum & Pembangunan, 2022)
The development of digital technology and information technology is happening very rapidly, computer systems are getting more sophisticated and internet access is getting easier making technology a part of people's daily lives, the existence of documents and or electronic information has now become a common thing. How does the Indonesian Civil Procedure Law regulates documents and or electronic information as an evidence and how does the law regulates the recognition, the validity and the strength of that evidence in the trials in order to create legal certainty for the people seeking justice.